Zwitterion Dual‐Modification Strategy for High‐Quality NiOx and Perovskite Films for Solar Cells - Wang, Xianzhao; Jiang, Jun; Liu, Ziyan; Li, Aijun; Miyasaka, Tsutomu; Wang, Xiao‐Feng (Small, 2024)
Nickel oxide (NiOx) has been limited in use as a hole transport layer for its low conduction, surface defects, and redox reactions with the perovskite layer. To address these issues, the incorporation of zwitterion L‐tryptophan (Trp) is proposed at the NiOx/Trp interface. The carboxyl group of Trp effectively passivates the surface positive defects of NiOx, thereby improving its optical and electrical properties. The ammonium group of Trp not only passivates negative defects but modulates the growth of the perovskite layer, resulting in an improved perovskite film quality. Furthermore, the Trp layer acts as a buffer layer, suppressing adverse interfacial reactions between the perovskite and NiOx. Consequently, perovskite solar cells with 1.56 and 1.68 eV absorbers achieve the champion power conversion efficiency (PCE) of 23.79% and 20.41%, respectively. Moreover, the unencapsulated devices demonstrate excellent long‐term stability, retaining above 80% of the initial PCE value after 1600 h of storage in the air with a humidity of 50–60%. To address severe issues in NiOx‐based perovskite solar cells, different kinds of amino acids are introduced at NiOx/perovskite interface. Research shows the L‐tryptophan with two kinds of charged groups has the superior dual‐passivation effect. With L‐tryptophan, the quality of NiOx and perovskite is improved. Besides, the performance and stability of devices is enhanced significantly.